PERTIMBANGAN HAKIM DALAM PENETAPAN DISPENSASI KAWIN AKIBAT HAMIL DILUAR NIKAH PADA PENGADILAN AGAMA KABUPATEN MALANG - Rossa Meilynda; Ahmad Subekti; Syamsu Madyan (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2021)
Marriage dispensation is a concession or waiver granted by the Religious Courts to prospective husbands and wives who do not meet the material requirements in marriage, namely they have not met the maximum age limit.The purpose of this study was to determine the basis of judges' considerations in determining marriage dispensation due to pregnancy outside of marriage at the Malang Regency Religious Court, Knowing the contents of the determination of the Malang Regency Religious Court Judge Council class in granting marriage dispensation applications due to pregnancy outside of marriage, What are the functions and duties of judges at the Court Religion. And the researchers took the research location at the Malang Regency Religious Court. In this research, the method used is descriptive method and qualitative approach. From the results of this study, it can be concluded that the Judge of the Religious Court of Malang Regency in determining the Marriage Dispensation is in accordance with existing regulations and has been guided by Law No. 48 of 2019 and uses the legal basis in accordance with Law No. 1 of 1974 concerning marriage, fiqiyah rules and the Compilation of Islamic Law.